Child Health and Parental Responses to an Unconditional Cash Transfer at Birth - Alexandra de Gendre; John Lynch; Aurélie Meunier; Rhiannon Pilkington; Stefanie Schurer (Institute of Labor Economics (IZA), 2021)
We estimate the impact on child health of the unanticipated introduction of the Australian Baby Bonus, a 3,000 one-off unconditional cash transfer at birth. Using regression discontinuity methods and linked administrative data from South Australia, we find that treated babies had fewer preventable, acute, and urgent hospital presentations—medical care available without co-payments—in the first two years of life. The payment later increased demand for elective care, which requires planning, medical referrals, and often co-payments. Our effects are strongest for disadvantaged families. Our findings suggest that up to 34% of the payout were recouped within the first year.
Keywords: I14; I38; 330; unconditional cash transfers; baby bonus; child health; health care utilization; regression discontinuity design; natural experiment; linked administrative data